Entrepreneurship and Family Role: A Systematic Review of a Growing Research - Cardella, Giuseppina Maria; Hernández-Sánchez, Brizeida Raquel; Sánchez García, José Carlos (Frontiers in Psychology, 2020)
In recent years, research on the family role and entrepreneurship has increased noticeably, consolidating itself as a valid and current subject of study. This paper presents a systematic analysis of academic research, applying bibliometric indicators, and cluster analysis, which define the state of research about the relationship between family role and entrepreneurship. For this purpose, using three well-accepted databases among the research community: Scopus, Web of Science, Business Source, a total of 92 articles were selected and analyzed, published between 1989 and 2019 (until March). A cluster analysis shows five main areas of literature development: (1) cultural dimension and geneder issue; (2) family business and succession; (3) parental role models and entrepreneurial intentions; (4) entrepreneurship and self-employment; (5) family support and women entrepreneurs. Findings also show how this is a relatively recent field of study, with a multidisciplinary character.